Factores económicos que influyen en el desempeño laboral de la clínica Sánchez Ferrer – Sanna, en la ciudad de Trujillo, región La Libertad, año 2017 - Marquina Chávez, Karen Lisbeth (2019)
The general objective of this research is to determine the influence of economic factors on the work performance of the Sánchez Ferrer clinic in Trujillo, La Libertad region, in 2017. This study is a non-experimental type of cross-sectional and correlational research, in which a logistic model was used. It was found that remuneration, seniority, travel time to go to work, academic degree, place of origin, work environment and organizational have a significant influence on performance of the collaborators in the year 2017. With respect to the logistic econometric model for the work performance of the Sánchez Ferrer Clinic; the evidence indicates that the variables included in the model explain by 65.76%. In addition, marginal effects were found: 5.2% for remuneration, 5.7% seniority, - 6.2% travel time to go to work, 14.14% academic degree, -17.35% place of origin, 5.62% labor and organizational climate. Finally, the estimated model presents a joint and individual stability of the estimated coefficients.